Ramos colaterais da aorta abdominal de cutias (Dasyprocta leporina Linnaeus, 1758) - Tertulino, Moisés Dantas (Universidade Federal Rural do Semi-Árido, 2021)
Dasyprocta leporina is a rodent, geographical distribution is restricted to the American continent. The objective of the present work was to describe the lateral branches of the abdominal aorta artery of the agouti. Eight agouti of both sexes from CEMAS, UFERSA were used to carry out the work, as per CEUA authorization opinion nº 16/2014. Anesthetic protocol was performed with ketamine hydrochloride and xylazine, followed by propofol. Reaching an anesthetic level, potassium chloride was administered for euthanasia. After death was confirmed, latex associated with barium was injected in the craniocaudal direction in one of the animals, and vinylite in another. The first animal was submitted to radiography and the second to corrosion. Another six animals were thawed and perfused with latex. The first collateral branch emitted was a celiac artery, an odd and large-caliber artery, which appeared ventrally and emitted the branches corresponding to the left gastric artery, hepatic artery and splenic artery. The second collateral branch was a cranial mesenteric artery, which originated ventrally in the abdominal aorta, caudal to the celiac artery. After a short path, the abdominal aorta emitted laterally as right and left renal arteries, these arteries emit the adrenal arteries, only one case where an adrenal artery directly from the aorta. The gonadal arteries originate from a single specimen in the same topography as the renal arteries and are more often caudal to the renal arteries. Near the entrance to the pelvic cavity, the abdominal aorta ventrally emitted a medium to fine vessel, the caudal mesenteric artery. The abdominal aorta at the entrance of the pelvic cavity dorsocaudally emitted its last collateral branch, a median sacral artery. It is concluded that the associated branches of the aorta account for the pattern common to anterior rodents
Keywords: Cardiovascula; Radiografia; Roedor; Vascularização; CIENCIAS AGRARIAS::MEDICINA VETERINARIA